Comparison of different blade types - Kleshnev, V. (BioRow, 2020)
The new measurement method of the blade centre of pressure, developed earlier (RBN 2020/10), was used for the comparison of various blade types made by Concept2: Smoothies (plain, 88/288), Fat2 (vortex 88/282) and the new Comps (vortex, 88/288). Three pairs of sculls with these blade types (Fig.1) were instrumented with four force torque sensors each as described before. It was originally planned to test the blades simultaneously with three single scullers, but due to illness, only one became available (1.84m, 85kg, international U23 level), who completed three 1000m runs with step-increasing stroke rate (20, 24, 28, 32, 38spm) changing the sculls after each run. Concluding, based on the limited data available, it looks like the Fat2 blade was the most efficient between the three types tested. The new Comp blade type showed a slightly better performance compared to the traditional Smoothies and were quite comfortable to row. These preliminary findings require further experiments and analysis to eliminate the random effect of the weather. Also, the effect of the Vortex strips should be studied. Though Fat2 blades appeared to be the most efficient, they were qualitatively the most uncomfortable to row, so more work could be done on the blade shape improvement.